2014
DOI: 10.1016/j.neuroimage.2014.03.051
|View full text |Cite
|
Sign up to set email alerts
|

The functional oculomotor network and saccadic cognitive control in healthy elders

Abstract: Decline in executive function is the most common age-associated cognitive deficit and may be a risk factor for neurodegenerative disease. The antisaccade (AS) task involves inhibition of a prepotent visuomotor response and is a well-validated executive function test in aging and neurodegeneration. We investigated the functional connectivity of the cortical oculomotor network during successful AS performance in healthy elders. Elevated BOLD activity in the right lateral frontal eye field (rlatFEF), a region lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 53 publications
0
22
0
1
Order By: Relevance
“…Other studies have shown that when the FEF is lesioned, the suppression of the reflexive pro-saccade remains intact, however, the ability to generate anti-saccades becomes impaired (Gaymard et al, 1998; Davidson et al, 1999). Furthermore, imaging results in healthy elderly subjects – more prone to decline in executive function – indicated that with cognitive decline FEF activity was associated with poor anti-saccade performance (Pa et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that when the FEF is lesioned, the suppression of the reflexive pro-saccade remains intact, however, the ability to generate anti-saccades becomes impaired (Gaymard et al, 1998; Davidson et al, 1999). Furthermore, imaging results in healthy elderly subjects – more prone to decline in executive function – indicated that with cognitive decline FEF activity was associated with poor anti-saccade performance (Pa et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Most of the direction errors made by elderly were initiated at longer latency, well beyond the express epoch for all but the 77-85 yo cohort (see insert in figures 4b and 5d), and could be more indicative of working memory performance than of inhibitory control. The changes in task performance that occur in the elderly have also been related to changes in functional connectivity in frontal cortex [56,57]. In summary, the different trajectories for the frequencies of…”
Section: Anti-saccade Behaviour Across the Lifespanmentioning
confidence: 99%
“…Other studies have shown then when FEF is lesioned, the suppression of the reflexive pro-saccade remains intact, however, the ability to generate anti-saccades is impaired (Gaymard et al, 1998;Davidson et al, 1999). Furthermore, imaging results in healthy elderly subjects more prone to a decline in executive function indicate after cognitive decline, the aged FEF activity was associated with poor anti-saccade performance (Pa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%